MEASURING USER SATISFACTION AND NET BENEFIT OF SAKTI SYSTEM: LESSONS FROM STAKEHOLDERS OF REGIONAL TREASURY OFFICE IN RIAU PROVINCE - Rahayu, Winarni; Sudarno, Sudarno; Komardi, Dadi (Jurnal Aplikasi Manajemen, 2023)
"User satisfaction" is always an important measure of a stakeholder's opinion of e-government and must cover the entire stakeholder experience. "Net benefits" are the most important success factor of implementation system information and can measure the balance of positive and negative impacts of the e-government like the SAKTI system. This study aims to analyze the influence of service quality, information quality, system quality, organizational support, and regulatory environment on user satisfaction and net benefits of SAKTI users. This quantitative study uses primary data in questionnaires distributed to respondents through google forms and interviews. The questionnaire used simple random sampling. The sample size in this study was 482. The data were analyzed by Structural Equation Modeling (SEM) using Partial Least Square (PLS), namely SmartPLS version 3.2.9. The hypothesis test results show that system quality significantly and strongly impacts user satisfaction. Information quality has a large and strong impact on user satisfaction. Service quality has a large and strong impact on user satisfaction. Organizational support has a small and weak impact on user satisfaction. The regulatory environment has a large and strong impetus for user satisfaction. User satisfaction, influenced by service quality, information quality, system quality, organizational support, and the regulatory environment, strongly impacts the net On Stakeholders of the Regional Treasury Office in Riau Province. The research model can use to conduct surveys of user satisfaction on SAKTI or other e-government and evaluate the results.